Viver-envelhecer do adolescente privado de liberdade na Fundação de Atendimento Sócio-Educativo - Nunes, Roger Egidio Brum (2018)
The adolescence is configured as a transition time, it is characterized by c hanges that can bring many challenges to those who experience it. If we add the condition of deprivation of freedom to the adolescence we will have an unpredictable context, that can affect the perception of oneself and influence especially the living and aging of this adolescent. Considering that the aging process is inherent to all human being and that takes place in a biopsychosocial dynamic of each subject and of the context in which they are inserted we sought to know the narratives of the adolescents in conflict with the law, who are in deprivation of freedom, on the aspects of their life trajectories that influence their living and their aging expectations. A research of qualitative, exploratory and descriptive approach, therefore, was developed, counting with 11 teenage boys, who comply with socio-educational measure of deprivation of freedom in a Unit of Socio-Educational Assistance Foundation, in a city in the interior of the state Rio Grande do Sul. The data collection has been raised through individual interviews, using narrative as methodological strategy. The information obtained passed through thematic analysis of content with the elaboration of categories. The importance of relationships in their life trajectory has been evident on their narrat ive. Among the intersubjective relations, key category, emerged the first family ties, passing through some named aspects about the deprivation of freedom feeling, financial aspects involved repeated risk behavior, perceptions about aging, expectation related to the future, as well as a certain deficit of healthy relations which permeated the teenagers' living -aging to the present moment. From the thematic analysis of content, the teenagers’ narratives bring us back to the significant interaction with the grandparents in the daily lives of inmates, having a strong affective influence on the development of young people and creating identification bonds that are absorbed indelibly in the psyche in different ways over time.